Incidence and Predictors of Incontinence-Associated Skin Damage in Nursing Home Residents With New-Onset Incontinence. Issue 2 (March 2017) - Bliss, Donna Z.; Mathiason, Michelle A.; Gurvich, Olga; Savik, Kay; Eberly, Lynn E.; Fisher, Jessica; Wiltzen, Kjerstie R.; Akermark, Haley; Hildebrandt, Amanda; Jacobson, Megan; Funk, Taylor; Beckman, Amanda; et al.
Abstract : PURPOSE: The purpose of this study was to determine the incidence and predictors of incontinence-associated dermatitis (IAD) in nursing home residents. METHODS: Records of a cohort of 10, 713 elderly (≥65 years) newly incontinent nursing home residents in 448 nursing homes in 28 states free of IAD were followed up for IAD development. Potential multilevel predictors of IAD were identified in 4 national datasets containing information about the characteristics of individual nursing home residents, nursing home care environment, and communities in which the nursing homes were located. A unique set of health practitioner orders provided information about IAD and the predictors of IAD prevention and pressure injuries in the extended perineal area. Analysis was based on hierarchical logistical regression. RESULTS: The incidence of IAD was 5.5%. Significant predictors of IAD were not receiving preventive interventions for IAD, presence of a perineal pressure injury, having greater functional limitations in activities of daily living, more perfusion problems, and lesser cognitive deficits. CONCLUSION: Findings highlight the importance of prevention of IAD and treatment/prevention of pressure injuries. A WOC nurse offers expertise in these interventions and can educate staff about IAD predictors, which can improve resident outcomes. Other recommendations include implementing plans of care to improve functional status, treat perfusion problems, and provide assistance with incontinence and skin care to residents with milder as well as greater cognitive deficits.